Analisis Pengendalian Kualitas Produk Benih Gurame pada CV Dejeefish - Amanda Aulia Zahirah; Reva Nadia Utami; Kayla Safa Irdinta; Rivaludin Rivaludin; Rizal Hasan Umarthalib (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Quality control of gourami fry is a crucial aspect in maintaining product quality and increasing the success rate of cultivation. This research, conducted at CV Dejeefish, aimed to identify the dominant types of defects in the gourami fry production process and analyze their causal factors using the 6M approach. Data collection was conducted using a checklist during January–April to record the frequency of emerging problems. The data was then analyzed using a Pareto diagram to identify the most significant problems, and a Fishbone diagram to map the root causes. The results showed that the most dominant type of defect was fish mortality, which accounted for 85.4% of the total problems. The main contributing factors included worker negligence, unstable water quality, suboptimal pond conditions, and poor packaging. The Fishbone analysis indicated that the root causes of the problems stemmed from weaknesses in methods, labor, equipment, and the environment. Therefore, improving the implementation of SOPs, worker training, standardizing measuring instruments, and environmental monitoring are strategic steps to improve the quality of gourami fry at CV Dejeefish.